Study on Cultivation of Wheat by Temperature Control with Adequate Irrigation in the Fields of South India - P.S., Jwala Priyadarshini (International Journal of Applied Sciences and Biotechnology, 2023)
This investigation was conducted during the Zaid season of 2023 to evaluate the performance of four wheat variants was conducted in the agricultural plots of Nindra Mandal, Chittoor District, Andhra Pradesh, India. (13.3831°N 79.6963°E). The experimental plots were laid out in open farming design with adjacent block design with for variants of wheat: Chhoti Lerma, Kalyan sona, Sharbati Sonora and Sonalika with control being GW173. Growth and yield were found to be good in open farming comprising the nutrient rich red soil with pH 5.6. Growth parameters viz. plant height, diameter and crown width were observed. Grain yield attributes like wheat germination count, leaf area index and plant height were found higher in Kalyan sona. Harvest Index and Nutrients in each variety have been recorded in which the grains of Kalyan sona and Sonalika showed to be compatible to be cultivated in summer. Int. J. Appl. Sci. Biotechnol. Vol 11(4): 181-185.